Vitamin D Receptor Activation Influences NADPH Oxidase (NOX2) Activity and Protects against Neurological Deficits and Apoptosis in a Rat Model of Traumatic Brain Injury. (19th December 2017) - Cui, Changmeng; Song, Sixin; Cui, Jianzhong; Feng, Yan; Gao, Junling; Jiang, Pei
Abstract : Traumatic brain injury (TBI) is a worldwide phenomenon which results in significant neurological and cognitive deficits in humans. Vitamin D (VD) is implicated as a therapeutic strategy for various neurological diseases now. Recently, inhibition of the NADPH oxidase (NOX2 ) was reported to protect against oxidative stress (ROS) production. However, whether alterations in NOX2 expression and NOX activity are associated with calcitriol (active metabolite of VD) treatment following TBI remains unclear. In the present study, rats were randomly assigned to the sham, TBI, and calcitriol-treated groups. Calcitriol was administered intraperitoneally (2  μ g/kg) at 30 min, 24 h, and 48 h after TBI insult. We observed that calcitriol treatment alleviated neurobehavioral deficits and brain edema following TBI. At the molecular levels, administration of calcitriol activated the expression of VDR and downregulated NOX2 as well as suppressed apoptosis cell rate in the hippocampus CA1 region of TBI rats. In conclusion, our findings indicate that the protective effects of calcitriol may be related to the modulation of NADPH oxidase and thereby ultimately inhibited the progression of apoptosis. Calcitriol may be promising as a protective intervention following TBI, and more study is warranted for its clinical testing in the future.